Prevalence and morphological evaluation of dens invaginatus with associated palatogingival groove in maxillary anterior teeth using cone-beam computed tomography: A retrospective study on an Eastern Indian cohort - P. Mondal; K. Mistry; T. Paul; K. K. Saha; D. Das; S. Das (Эндодонтия Today, 2025)
INTRODUCTION. Developmental anomalies like dens invaginatus (DI) and palatogingival groove (PGG) increase susceptibility to pulpal and periradicular diseases, complicating root canal treatment. Advanced imaging modalities such as cone-beam computed tomography (CBCT) provide enhanced visualization, aiding in accurate diagnosis and treatment planning. AIM. This study aimed to determine the prevalence and characteristics of DI and associated PGG in maxillary anterior teeth among an Indian population. MATERIALS AND METHODS. A retrospective cross-sectional study was conducted on 586 CBCT scans recorded for clinical purposes, of which 228 met the inclusion criteria. CBCT images were analyzed for DI and associated PGG using Oehler’s and Gu’s classifications. Data were statistically analyzed, with significance set at p ≤ 0.05. RESULTS. DI was observed in 33 teeth (2.41%), predominantly in lateral incisors (6.14%). Oehler’s Type I was the most common variant (78.8%). PGG was present in 8 teeth (24.24%), all of which classified as Gu’s Type I in the teeth where DI was detected. Unilateral involvement of DI (56.5%) was more frequent than bilateral involvement (43.5%). No significant gender differences were noted for DI or PGG prevalence. CONCLUSIONS. The prevalence of DI and associated PGG highlights the need for advanced diagnostic tools like CBCT to facilitate early detection and management. CBCT’s three-dimensional imaging capabilities are indispensable for diagnosing these anomalies and improving treatment outcomes.